Efektivitas Ceftazidime-Avibactam terhadap Bakteri Gram Negatif Penghasil Enzim Karbapenemase - Ade Dharmawan; Nicolas Layanto (Jurnal MedScientiae, 2022)
Antibiotic therapy is a major concern in the health sector. There is an increase in the resistance of gram-negative bacteria that produce carbapenemase enzymes to certain antibiotics, especially the β-lactam group, thus creating a new challenge for the health world to find stronger antibiotics to fight the resistance of these gram-negative bacteria. Currently, there are several new antibiotics that have been approved as treatment options, such as Ceftazidime-Avibactam. It is hoped that this new treatment can be an option, especially for gram-negative bacteria that produce carbapenemase enzymes.